Experience of sexual self-esteem among men living with HIV. (February 2017) - Rohleder, Poul; McDermott, Daragh T; Cook, Rachel
Much of the focus on sexual health for people living with HIV has been on promoting safe sex behaviours. However, also important for sexual health is a positive sexual self-esteem. This article reports on an interpretative phenomenological analysis of interviews with seven men about the impact that having HIV has had on their sense of sexual self. Five overarching themes were identified: the 'destruction' of a sexual self; feeling sexually hazardous; sexual inhibition; reclaiming a sexual self and finding a place through sero-sorting. With HIV now being a chronic illness, interventions are required to support people to lead sexually satisfying lives.